Implementasi Media Pembelajaran Interaktif Berbasis Canva untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas VI SDN 45 Mataram - Zahrawani, Ina Ayu Zahrawani; Amrullah; Maskur (Mataram University, 2025)
This classroom action research aims to improve the learning outcomes of sixth-grade students at SDN 45 Mataram through the implementation of interactive learning media based on Canva. The study was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects were 32 students of class 6A. Data were collected through learning achievement tests, observations, and documentation. The results showed that the use of Canva-based interactive learning media in the IPAS subject, particularly on the topic How Our Body Moves, was effective in enhancing students’ understanding of the skeletal, joint, and muscular systems. The improvement was evident from the significant increase in students’ average scores from cycle I to cycle II, accompanied by higher levels of active participation during the learning process. These findings indicate that Canva-based interactive learning media not only improve learning outcomes but also foster active student engagement, making it an innovative solution for teaching IPAS.